Eating and Marketing Cultured Meat is a Jurisprudential Study - Mansour, Heba (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to define the concept of cultured meat, its history, and reasons for using it, explain how it is produced, and highlight the health effects of its consumption, leading to the conclusion of the legal rulings related to it. Methods: The research followed an inductive approach to the concept of cultured meat. It employed the analytical method to analyze the scientific texts on the subject and to examine the stages of production and the materials used. The research also utilized a deductive approach to conclude the general and detailed legal rulings on producing, consuming, and marketing cultured meat. Results: The research concluded that cultured meat can be defined as meat produced and manufactured in a laboratory using animal stem cells so that it is comparable to livestock meat, without the slaughter of the animal. This process is considered a form of biological physical asexual cloning, based on tissue engineering and genetic engineering. Parts of the complex process of producing cultured meat are permissible, starting with obtaining and utilizing stem cells and applying tissue engineering to them within the controls set by scientists, as well as the permissibility of animal cloning under its conditions. Conclusions: It is permissible to manufacture, consume, and market cultured meat that meets the legal, medical, and marketing controls referred to in the research. If any defect is found in these controls, it will be deemed forbidden in terms of manufacturing, consumption, and marketing alike.